Relations between basic milk components and free fatty acid content in Holstein cow milk as lipolysis parameter - Luděk Stádník; Jaromír Ducháček; Renáta Toušová; Jan Beran; Martin Ptáček; Lenka Kouřimská (Mljekarstvo)
The aim of this study was to evaluate in detail the relationship between the basic milk components (fat and protein percentage) and the free fatty acids (FFA) content, as indicators of spontaneous and/or induced lipolysis. The additional aim of the study was to compare the FFA content of milk with respect to spontaneous and induced lipolysis. Milking was carried out in herringbone parlour twice a day. In total, 540 milk samples were obtained for evaluation of spontaneous (n=240) and induced lipolysis (n=300). The milk samples for determination of basic milk components and FFA (li¬polysis) levels were collected during four subsequent lactation weeks. Milk samples for spontaneous lipolysis detection were taken directly in parlour immediately after milking using the ICAR methodology and subsequently grouped. Induced lipolysis was observed from bulk milk in time 0, 1, 2, 3, and 4 hours after milking (T0-T4). The evaluation of basic components and FFA content was carried on MILKOSCAN F120 (Foss Electronic; Denmark). Statistical evaluation was carried out using SAS 9.3. (SAS/STAT® 9.3, 2011). An increase of one percentage of milk fat was equal to 0.318 mmol x 100 g-1 FFA decline (spontaneous lipolysis) or from 0.232 to 0.370 mmol x 100 g-1 FFA decline (induced lipolysis T0-T4) respectively. One percentage increase of milk protein was equal to 1.219 mmol x 100 g-1 FFA increase (spontaneous lipolysis) or 0.421 to 1.531 mmol x 100 g-1 FFA decrease (induced lipolysis T0 - T4) respectively. Significant differences (P<0.01) were detected among FFA content in relation to spontaneous and induced lipolysis evaluated during storage and cooling after milking. The minimal differences were detected between the FFA content during 4 hours cooling and storage of milk in the tank.